2016
DOI: 10.1038/srep38331
|View full text |Cite
|
Sign up to set email alerts
|

BHX Inhibits the Wnt Signaling Pathway by Suppressing β-catenin Transcription in the Nucleus

Abstract: BHX (N-(4-hydroxybenzyl)-1,3,4-triphenyl-4,5-dihydro-1H-pyrazole-5-carboxamide), a Wnt signaling pathway inhibitor, effectively inhibits tumor cell growth, but the underlying mechanism is unclear. Thus, we aim to investigate the effects and associated mechanism of BHX action on A549 and MCF-7 cell lines. In our study, MTT(3-[4,5-dimethyl-2-thiazolyl]-2,5-diphenyl-2H-tetrazolium bromide) and xenograft model assay indicated that cell growth was inhibited by BHX at a range of concentrations in vitro and in vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Validating our hypothesis that CDH11 may promote β-catenin nuclear translocation and WNT activation, we demonstrated that CDH11 modulates β-catenin expression levels and that CDH11/β-catenin signalling axis plays a regulatory role for the canonical WNT signalling pathway in TNBC (Figure 3), as concomitant decreased CDH11 and β-catenin in the TNBC cell was observed, with siCDH11 cells exhibiting reduced CDH11/β-catenin nuclear co-localization compared to the control WT cells (Figure 4). This is consistent with studies suggesting that the transcriptional suppression of β-catenin was associated with inhibition of the WNT signalling activity in MCF-4 and A549 cell lines [31]. Based on our immunofluorescence and IHC staining, CDH11 localizes in the membrane and cytoplasm.…”
Section: Discussionsupporting
confidence: 92%
“…Validating our hypothesis that CDH11 may promote β-catenin nuclear translocation and WNT activation, we demonstrated that CDH11 modulates β-catenin expression levels and that CDH11/β-catenin signalling axis plays a regulatory role for the canonical WNT signalling pathway in TNBC (Figure 3), as concomitant decreased CDH11 and β-catenin in the TNBC cell was observed, with siCDH11 cells exhibiting reduced CDH11/β-catenin nuclear co-localization compared to the control WT cells (Figure 4). This is consistent with studies suggesting that the transcriptional suppression of β-catenin was associated with inhibition of the WNT signalling activity in MCF-4 and A549 cell lines [31]. Based on our immunofluorescence and IHC staining, CDH11 localizes in the membrane and cytoplasm.…”
Section: Discussionsupporting
confidence: 92%
“…In the treatment group, H460 cells were implanted in BALB/c (nude) mice via subcutaneous injection. For the positive control, BALB/c (nude) mice were injected with cisplatin [23]. Growth of the implanted tumors was significantly inhibited in the cisplatin group; however, the body weights of the cisplatin-mice decreased rapidly.…”
Section: Sfp Inhibits the Proliferation Of Lung Cancer Cells In Vitromentioning
confidence: 99%
“…Specific phosphorylation on Ser552 or Ser675 on the C-terminus of β-catenin by PKA leads to an increase in nuclear translocation of β-catenin and subsequently enhanced TCF/ LEF transcriptional activity in many cell types 13 , 14 . Aberrant accumulation of β-catenin in nucleus caused by Wnt gene mutations in CRC is thus a potential target to search for specific chemotherapeutic agents 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%